Development and validation of molecular markers for characterization of Boehmeria nivea var. nivea and Boehmeria nivea var. tenacissima - Lee Cheng-Yu; Tong Teng-Soung; Chiou Shu-Jiau; Li Chuan-I; Lee Lain-Tze; Cheng Ching-Ming (BMC, 2010)
Abstract Background The root of Boehmeria spp (ramie) is a hepatoprotective Chinese herbal medicine. Medicinal properties vary between Boehmeria nivea var. nivea and Boehmeria nivea var. tenacissima, which are local species found in Taiwan. As commercial preparations may use either species, there is a need for a rapid and simple assay to identify variants for quality control. Methods Four methods were developed and tested for their applicability in differentiating the two species. These methods were random amplified polymorphic DNA (RAPD); sequence characterized amplified regions (SCAR); single nucleotide polymorphisms (SNP) and cleaved amplified polymorphic sequences (CAPS). Results Three RAPD markers were developed that produced unique bands in B. nivea var. tenacissima and B. nivea var. nivea. Based on sequenced RAPD bands, one SCAR marker was developed that produced a single DNA band in B. nivea var. nivea. Two SNP markers differentiated between B. nivea var. nivea and B. nivea var. tenacissima based on single nucleotide substitutions. A pair of CAPS oligonucleotides was developed by amplifying a 0.55-kb DNA fragment that exhibited species-specific digestion patterns with restriction enzymes Alf III and Nde I. Consistent results were obtained with all the four markers on all tested Boehmeria lines. Conclusion The present study demonstrates the use of the RAPD, SCAR, SNP and CAPS markers for rapid identification of two closely related Boehmeria species.